FRI0378 GENERAL SAFETY AND TOLERABILITY OF SUBCUTANEOUS TANEZUMAB FOR THE TREATMENT OF OSTEOARTHRITIS: A POOLED ANALYSIS OF RANDOMIZED, PLACEBO-CONTROLLED TRIALS. (2nd June 2020) - Berenbaum, F.; Schnitzer, T.; Kivitz, A.; Viktrup, L.; Hickman, A.; Pixton, G.; Brown, M.; Davignon, I.; West, C.
Abstract : Background: Tanezumab, a monoclonal antibody against nerve growth factor, is in development for the treatment of signs and symptoms of osteoarthritis (OA). Objectives: To assess the safety and tolerability of subcutaneous (SC) tanezumab in patients with OA. Methods: Data were derived from 3 randomized placebo-controlled OA trials. SC treatment (every 8 weeks for 16–24 weeks with 8–24 week follow-up) included placebo, tanezumab 2.5 mg, tanezumab 2.5/5 mg (2.5 mg at day 1 and 5 mg at week 8), and tanezumab 5 mg. Overall treatment-emergent adverse events (TEAEs) and TEAEs of abnormal peripheral sensation were pooled from all 3 trials (placebo N = 586; tanezumab: 2.5 mg N = 602, 2.5/5 mg N = 219, 5 mg N = 347). Pre-specified TEAEs potentially associated with sympathetic neuropathy (anhidrosis, bradycardia, hypohidrosis, orthostatic hypotension, or syncope) and pre-specified joint events (primary osteonecrosis, rapidly progressive OA [RPOA] type 1 or type 2, subchondral insufficiency fracture, or pathological fracture; adjudicated by an independent committee of experts) were pooled from the 2 trials that included prospective evaluation of sympathetic and joint safety (placebo N = 514; tanezumab: 2.5 mg N = 528, 2.5/5 mg N = 219, 5 mg N = 284). TEAEs are presented for the treatment period; joint safety is presented for the full study (treatment plus follow up) period. Results: Patient demographics (80.7% white, 66.8% female, mean age ≈ 63 years) and clinical characteristics were similar across groups. TEAE rates were: placebo = 51.7%, tanezumab 2.5 mg = 52.3%, tanezumab 2.5/5 mg = 47.0%, and tanezumab 5 mg = 54.8%. Of TEAEs occurring in ≥2% of patients in any group, only oedema peripheral, joint stiffness, and paraesthesia had a higher incidence (95% confidence interval excluded 0) in any tanezumab group relative to placebo. Serious TEAE rates were: placebo = 1.5%, tanezumab 2.5 mg = 2.2%, tanezumab 2.5/5 mg = 1.4%, and tanezumab 5 mg = 2.6%. Rates of treatment and/or study discontinuation due to TEAEs were: placebo = 2.2%, tanezumab 2.5 mg = 1.8%, tanezumab 2.5/5 mg = 0.5%, and tanezumab 5 mg = 1.4%. Only arthralgia and OA led to discontinuation in >1 patient in any group. TEAEs of abnormal peripheral sensation rates were: placebo = 2.2%, tanezumab 2.5 mg = 5.1%, tanezumab 2.5/5 mg = 3.2%, and tanezumab 5 mg = 6.1%. Paraesthesia and hypoaesthesia were the most common events. Potential sympathetic neuropathy TEAE rates were: placebo = 0.8%, tanezumab 2.5 mg = 1.5%, tanezumab 2.5/5 mg = 0.5%, and tanezumab 5 mg = 2.8%; exposure-adjusted rates were not statistically different between any tanezumab group and placebo. Bradycardia and orthostatic hypotension were the most common events. No patient was considered to have a sympathetic neuropathy. TEAEs of abnormal peripheral sensation and potential sympathetic neuropathy were mostly mild and resolved. Joint safety event rates were statistically different for tanezumab 5mg (3.2%), but not 2.5mg (1.9%) or 2.5/5mg (0.5%), compared to placebo (0%). RPOA type-1 was the most common event. Total joint replacement rates were: placebo = 4.5%, tanezumab 2.5 mg = 5.9%, tanezumab 2.5/5 mg = 6.8%, and tanezumab 5 mg = 7.0%; rates were not statistically different between any tanezumab group and placebo. Conclusion: Tanezumab was generally safe and well tolerated in most patients, with rates of overall TEAEs and treatment/study discontinuations similar to placebo and no evidence of a sympathetic safety signal. TEAEs of abnormal peripheral sensation and joint safety events were infrequent but more common with tanezumab than placebo. Disclosure of Interests: Francis Berenbaum Grant/research support from: TRB Chemedica (through institution), MSD (through institution), Pfizer (through institution), Consultant of: Novartis, MSD, Pfizer, Lilly, UCB, Abbvie, Roche, Servier, Sanofi-Aventis, Flexion Therapeutics, Expanscience, GSK, Biogen, Nordic, Sandoz, Regeneron, Gilead, Bone Therapeutics, Regulaxis, Peptinov, 4P Pharma, Paid instructor for: Sandoz, Speakers bureau: Novartis, MSD, Pfizer, Lilly, UCB, Abbvie, Roche, Servier, Sanofi-Aventis, Flexion Therapeutics, Expanscience, GSK, Biogen, Nordic, Sandoz, Regeneron, Gilead, Sandoz, Thomas Schnitzer Consultant of: Pfizer, Lilly, AstraZeneca, GSK, Alan Kivitz Shareholder of: AbbVie, Amgen, Gilead, GSK, Pfizer Inc, Sanofi, Consultant of: AbbVie, Boehringer Ingelheim, , Flexion, Genzyme, Gilead, Janssen, Novartis, Pfizer Inc, Regeneron, Sanofi, SUN Pharma Advanced Research, UCB, Paid instructor for: Celgene, Genzyme, Horizon, Merck, Novartis, Pfizer, Regeneron, Sanofi, Speakers bureau: AbbVie, Celgene, Flexion, Genzyme, Horizon, Merck, Novartis, Pfizer Inc, Regeneron, Sanofi, Lars Viktrup Shareholder of: Eli Lilly and Company, Employee of: Eli Lilly and Company, Anne Hickman Shareholder of: Pfizer Inc, Employee of: Pfizer Inc, Glenn Pixton Shareholder of: Pfizer Inc, Employee of: Pfizer Inc, Mark Brown Shareholder of: Pfizer Inc, Employee of: Pfizer Inc, Isabelle Davignon Shareholder of: Pfizer, Employee of: Pfizer, Christine West Shareholder of: Pfizer Inc, Employee of: Pfizer Inc